InterAlia : pismo poświęcone studiom queer (InterAlia, 2006)
"InterAlia, a peer-reviewed scholarly journal for queer theory, is open to submissions from a wide range of fields, written in English, Spanish, or Polish. Among the issues we hope our contributors will address is the translatability of queer concepts across cultural and linguistic borders; the relationship between queer theory and activism; the possibility of reconciling the different positionings within the queer community that are related to such factors as gender, race, class, age, sexual practices, and geographical location; the relevance of queer studies for understanding the discourses, cultural practices, and institutions that surround us; and the potential of queer as a counterdiscourse or counterpractice. We also publish (without the peer-review process) literary and art works, documentation of artistic and theatrical works, book reviews, manifestoes, theory-fiction, commentaries and other materials that fall outside the rigid academic standards."--About InterAlia page (English version, viewed June 13, 2023).
Keywords: Gay and lesbian studies : Periodicals; Homosexuality : Periodicals; Queer theory : Periodicals; Gay people : Periodicals; Lesbians : Periodicals; Homosexualité : Périodiques; Théorie queer : Périodiques; Homosexuels : Périodiques; Lesbiennes : Périodiques; Gay and lesbian studies; Homosexuality; Lesbians; Queer theory